2002
DOI: 10.1002/qre.480
|View full text |Cite
|
Sign up to set email alerts
|

Testing for software vulnerability using environment perturbation

Abstract: SUMMARYWe describe a methodology for testing a software system for possible security flaws. Based on the observation that most security flaws are caused by the program's inappropriate interactions with the environment, and are triggered by a user's malicious perturbation on the environment (which we call an environment fault), we view the security testing problem as the problem of testing for the fault-tolerance properties of a software system. We consider each environment perturbation as a fault and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Most implementations of this approach, such as [16] and [17], view the security testing problem as the problem of testing for the fault-tolerance properties of a software system. They consider each environment perturbation as a fault and the resulting security compromise a failure in the toleration of such faults.…”
Section: Related Workmentioning
confidence: 99%
“…Most implementations of this approach, such as [16] and [17], view the security testing problem as the problem of testing for the fault-tolerance properties of a software system. They consider each environment perturbation as a fault and the resulting security compromise a failure in the toleration of such faults.…”
Section: Related Workmentioning
confidence: 99%
“…Modeling a realistic installation suggests that error-caused vulnerabilities is a non-negligible source for security concerns. Du and Mathur [2000] injected errors in the environment of an application and observed the applications for security violations. NFTAPE has been used to inject control flow bit-flips in the user authentication section of sshd and ftpd on Linux and it was found that such faults may open up the affected servers for vulnerabilities [Xu et al, 2001].…”
Section: Fault Injectionmentioning
confidence: 99%
“…To ensure that every link l has a consistent interpretation of c l , every node has to calibrate c l with respect to an agreed-upon definition of an attack. Also, to enable us to interpret c l as a probability or proportion, we require that 0 ≤ c l ≤ 1 for every link l ∈ L. With an agreed-upon attack model, every node u can then determine in advance c l for each of its own outgoing links l ∈ L(u), where L(u) is the set of all outgoing links of node u, using vulnerability modeling [10], statistical measurements of reliability indexes [15], or security monitoring systems [26]. We point out that if an accurate estimate of c l is not available, we can set c l = 1, meaning that link l has all its data lost when it is under attack, and our analysis still applies to this worst-case scenario.…”
Section: Problem Formulationmentioning
confidence: 99%